Investigation on the Achievable Flow Length in Injection Moulding of Polymeric Materials with Dynamic Mould Tempering - Steve Meister; Dietmar Drummer (The Scientific World Journal)
A variety of parts in microsystems technology are manufactured by injection moulding of polymeric materials. In Particular the high cooling velocity affects negatively the process and the resulting part properties. The scope of this paper is to investigate the influence on the reachable flow length in injection moulding of different polymeric materials. The results indicate that the mould temperature has less impact on the achievable flow length of the polymer melt as the injection pressure. A higher mould temperature leads only to a slight increase in flow length. In addition, a transcending of the glass or the crystallization temperature of polymeric materials with the mould temperature shows no effect on the achievable flow length of the material.